Uma revisão sobre os produtos naturais com potencial acaricida frente ao carrapato Rhipicephalus sanguineus (Latreille 1806) - AGUIAR, Alexander Silva (Universidade Federal do Oeste do Pará, 2024)
Ticks are obligatory arthropods hematophagous presenting wide distribution and transmission of various diseases to humans through the association with bacteria, viruses, protozoa among others. Rhipicephalus sanguineus initially described in 1806 by Latreille, as Ixodes sanguineus, is a tick considered the most common ectoparasite in dogs. The most common harbourer diseases are babesiosis caused by Babesia vogeli and erlichiosis caused for agent Ehrlichia canis which can lead the dog to develop depression, fever and anorexia. The formulations developed for the control of this type of parasits besides causing resistance to the ticks due to its continuous use, have toxicological effects that must be taken into consideration, since these substances (isoxazolines) may accumulate in non-target organisms leading to larger consequences both for the health of the animal and for the environment in which it lives. As a more effective alternative to reduce these damage, the use of medicinal plants has been used to eliminate or reduce the action of these parasites. Plants are recognized as a rich source of biologically active extracts, essential oils and isolates. Scientific reports on the use of medicinal plants such as Sapindus saponária, Hyptis suaveolens (L.) Poit e Lippia sidoides with acaricidal action have intensified in the last decade aiming at the search for active principle for the control of ectoparasites. Given this, this literature review aims to contribute to the knowledge about the use of medicinal plants with acaricidal potential already reported in the last 12 years.